1996
DOI: 10.1021/ic9507530
|View full text |Cite
|
Sign up to set email alerts
|

Hexacoordinate Phosphorus. 7. Synthesis and Characterization of Neutral Phosphorus(V) Compounds Containing Divalent Tridentate Diphenol Imine, Azo, and Thio Ligands

Abstract: The reactions of bis(trimethylsilyl)ated forms of the Schiff base ligands N-(2-hydroxyphenyl)salicylideneamine {(HO)C(6)H(4)N(CH)C(6)H(4)(OH)}, N-(4-tert-butyl-2-hydroxyphenyl)salicylideneamine {(HO)((t)Bu)C(6)H(3)N(CH)C(6)H(4)(OH)}, N-(2-hydroxy-4-nitrophenyl)salicylideneamine {(HO)(O(2)N)C(6)H(3)N(CH)C(6)H(4)(OH)}, and the structurally related ligand 2,2'-azophenol with halogeno- and (trifluoromethyl)halogenophosphoranes yield a series of neutral hexacoordinate phosphorus(V) compounds by means of trimethylsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 13 publications
0
46
0
5
Order By: Relevance
“…Like that for oxyphosphoranes, recent studies have shown that phosphates (20 and 21) 49 and phosphites (22)(23)(24)(25) 48,49 displayed in Chart 3 will coordinate with sulfur donor atoms present in the same flexible eight-membered ring system that was discussed above. The P-S distances span 3.177(2) to 2.816(2) Å.…”
Section: Pentacoordinate Phosphorus Via Donor Actionmentioning
confidence: 87%
See 1 more Smart Citation
“…Like that for oxyphosphoranes, recent studies have shown that phosphates (20 and 21) 49 and phosphites (22)(23)(24)(25) 48,49 displayed in Chart 3 will coordinate with sulfur donor atoms present in the same flexible eight-membered ring system that was discussed above. The P-S distances span 3.177(2) to 2.816(2) Å.…”
Section: Pentacoordinate Phosphorus Via Donor Actionmentioning
confidence: 87%
“…As illustrated in Chart 1, most of the previous work 3,11,[25][26][27][28][29] has concentrated on restricted cyclic systems such that little flexibility existed in fixing the coordination site. By way of contrast, we have utilized more flexible ring systems containing the donor group which allows for different kinds of geometries and ring conformations.…”
Section: Hexacoordinate Phosphorusmentioning
confidence: 99%
“…In 1996, Cavell described the synthesis of neutral P(VI) compound 37 containing a divalent tridentate diphenol imine ligand and three chlorine atoms by the reaction of a bis silylated Schiff base with PCl 5 to give 37 after elimination of two equivalents of Me 3 SiCl (Scheme 7) [51]. 12 S. Constant · J. Lacour…”
Section: Via P-n Interactionmentioning
confidence: 99%
“…The use of tridentate ligands in coordination chemistry provides a facile means to stabilize transition metals [25] and main group elements [26] taking advantage of the chelate effect. Thus, it has been reported that tridentate ligands having an ONO donor set of atoms react with main group elements to give stable heterocycles [27].…”
Section: Introductionmentioning
confidence: 99%